Biology and the Subject: a re-conceptualization of the Lacanian Subject with regards to modern advances in biology and neurosciences; and its implications for political theory - Koen, Riekert (My University, 2021)
In political theory, and the social sciences more broadly, a fierce debate has been raging for many years, between essentialism and constructionism. This debate seems to pit two incompatible positions against one another and plays itself out in various different fields in social science. This dissertation focuses specifically on this debate being played out between Queer activists and Queer theorists who both represent examples of the essentialist and constructionist sides of the debate. By using the Lacanian subject as a starting point, this dissertation attempts to challenge this dichotomy. It does so by re-reading Lacan and showing how we can locate room for biology and scientific knowledge in his subject formation. This dissertation argues that he was neither ‘anti-science’ nor ‘anti-biology’ as is often claimed, and that a rereading of his process of subject formation with biological influences is possible. Reading the subject in this manner, we can incorporate modern neuroscience, biology and ‘neuropsychoanalysis’ into the Lacanian subject in such a way that it is not a victim to biological determinism or reductionism, or ‘determinate’ social constructionism. This modern conceptualization of the Lacanian subject has profound implications, as is illustrated by the aforementioned fissure between Queer activism and Queer theory
A research report submitted to the Faculty of Humanities, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Masters of Arts (Political Studies)